2012
DOI: 10.1074/jbc.m111.281485
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of Nel, a Thrombospondin-1-like Glycoprotein Involved in Neural Development and Functions

Abstract: Background: Nel is a multimodular glycoprotein and plays important roles in neural development and functions. Results: The N-terminal thrombospondin-1 domain is involved in multimer formation and heparin-and retinal axon-binding. Cysteine-rich domains bind to and inhibit retinal axons. Conclusion: Different molecular interactions and functions are mediated by distinct domains of Nel. Significance: The findings provide insights into how Nel exerts diverse functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 34 publications
(36 reference statements)
3
40
0
Order By: Relevance
“…Interestingly, even though Nell1 and Nell2 genes are highly expressed in brain and share 72% similarity in at amino acid sequence level, the biological functions of Nell1 and Nell2 proteins differ significantly. Nell2 was shown to support the survival of neurons from hippocampus and cerebral cortex and to function as a negative regulator of neuronal activity and as Nell2 deficient mice had a significant enhancement of long-term potentiation in the dentate gyrus [103][104][105]. It was recently shown that Nell2 can regulate axon guidance by functioning as a ligand for Robo3 receptor [106].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, even though Nell1 and Nell2 genes are highly expressed in brain and share 72% similarity in at amino acid sequence level, the biological functions of Nell1 and Nell2 proteins differ significantly. Nell2 was shown to support the survival of neurons from hippocampus and cerebral cortex and to function as a negative regulator of neuronal activity and as Nell2 deficient mice had a significant enhancement of long-term potentiation in the dentate gyrus [103][104][105]. It was recently shown that Nell2 can regulate axon guidance by functioning as a ligand for Robo3 receptor [106].…”
Section: Discussionmentioning
confidence: 99%
“…Nell1 protein is structurally similar to thrombospondin-1 and contains several structural motifs, including an N-terminal thrombospondin-1-like (TSPN) domain, coiled-coil (CC) domain, four von Willebrand factor type C (VWC) domains, and six epidermal growth factor (EGF)-like domains [57,105,107]. Mechanistically, Nell1 was shown to transduce osteogenic signals through the Ras-MAPK and Runx2 pathways [108] and Runx2 [109,110] although Nell1 was also found as a direct target of Osterix [111].…”
Section: Discussionmentioning
confidence: 99%
“…The highest expression levels are observed in the hippocampus and cerebral cortex, followed by the olfactory bulb and hypothalamus, and finally by the thalamus, cerebellum, and medulla oblongata. Many studies have shown that NELL2 plays an important role in nerve growth, neural differentiation, neural plasticity, synaptic transport, and vesicle release (Nelson et al, 2004;Choi et al, 2010;Nakamura et al, 2012;Munemasa et al, 2012). Ha et al (2008) found that NELL2 mRNA was highly expressed in the medial basal hypothalamus in female rats during the pubescent growth period.…”
Section: Discussionmentioning
confidence: 99%
“…The NELL1 and NELL2 genes are predominantly expressed in the brain and also show partly overlapping expression patterns (5). These genes have 72% similarity in their deduced amino acid sequences.…”
mentioning
confidence: 99%
“…NELL1 contains several structural motifs, including an N-terminal TSP-1-like (TSPN) domain, a coiled-coil (CC) domain, four von Willebrand factor type C (VWC) domains, and six EGF-like domains. The TSPN domain of NELL1 has been shown to have a heparin-binding activity that may be important for interaction with heparan sulfate proteoglycans to modulate cell-matrix interactions or cell function (3,5). The EGF-like domains of NELL1 were identified as binding sites for the protein kinase C ␤I subunit, suggesting a novel mode of action of NELL1; that is, functions in the cytoplasm (24).…”
mentioning
confidence: 99%